The Genesis of Accounting in Indonesia: The Dutch Colonialism in the Early 17th Century - Sukoharsono, E.G.; Gaffikin, Michael J.R. (The International Journal of Accounting and Business Society, 1993)
The concern of this paper is historical:Â  it is an inquiry into aspects of the emergence of accounting in Indonesia.Â  Although the earliest forms and use of money can be traced back to the Moslem (the 7th century) and even the Hindu (the 4th century) periods in Indonesia, little evidence has been found to indicate the early development of record-keeping. It is argued that the early establishment of the Dutch East Indies Company (1609), undoubtedly, is a starting point in the adoption of modern techniques of bookkeeping and that its development has been heavily moulded by the political, social, and economic penetration of Dutch colonialism in Indonesia. Keywords: Indonesian Accounting History, Foucauldian Perspective, Archaeology of Knowledge, Dutch East Indies Company.